PROFITABILITAS, LIKUIDITAS DAN INTELLECTUAL CAPITAL SEBAGAI DETERMINAN KINERJA KEUANGAN BADAN LAYANAN UMUM - Nurul Islami Mubarok; Nugraeni Nugraeni (LPPM STIE Muhammadiah Bandung, 2025)
This study investigates the determinants of financial performance in the under-researched Goods/Other Services cluster technical sub-cluster of Indonesian Public Service Agencies (BLUs). Although BLUs were formed to enhance public service delivery through greater financial flexibility, the factors driving their financial self-sufficiency in specialized sectors remain unclear. Using a quantitative approach with multiple linear regression, this research analyzes a balanced panel dataset from eight BLUs over the 2018-2023 period (48 firm-year observations). Financial performance is measured by the ratio of operational revenue to operational expenses (POBO). The findings reveal that profitability (Revenue on Asset - RoA) has a significant positive effect on financial performance, confirming that efficient asset utilization is crucial. Conversely, liquidity (Current Ratio) exhibits a significant negative effect, suggesting that excessive holdings of liquid assets act as a performance drag due to high opportunity costs. Most notably, Intellectual Capital (Value Added Intellectual Coefficient - VAIC) shows no significant impact, challenging the universal applicability of intangible asset theories in this asset-heavy, public sector context. This study concludes that strategies focused on cost efficiency, revenue optimization, and prudent cash flow management will yield the quickest and most measurable results. Investment in intellectual capital remains necessary as a long-term strategy; however, its impact may not be immediately apparent.